"As far as I'm concerned it'll be a clean campaign" [Joh Bjelke-Petersen] - Pryor, Geoff, 1944- (1987)
Joh Bjelk-Petersen, who has Canberra ambitions (much to the consternation of Opposition Leader John Howard), is on a visit to Los Angeles (the home of Disneyland) to open a Queensland tourism office. He is caught napping when Bob Hawke announces a federal election. --Information provided by Geoff Pryor.
Title devised by cataloguer.
Published in the Canberra Times on 28 May 1987.
Part of the Pryor collection of cartoons and drawings.
Also available online
Keywords: Bjelke-Petersen, Joh, -- Sir, -- 1911- 2005 -- Caricatures and cartoons; Elections -- Australia -- Caricatures and cartoons; Premiers -- Queensland -- Caricatures and cartoons; State and Territory politicians